DEFICITS DE SOUTIENS ET DIFFICULTES D’ADAPTATION PSYCHOSOCIALE CHEZ LES ELEVES-MERES A ABIDJAN - Opadou Koudou; Casimir Zady; Edwige Marina G. Kouamé N’guessan (European Scientific Journal, ESJ, 2015)
This study has for objective to estimate the effects of the deficits of supports on the difficulties of psychosocial adaptation of pupil-mother. The site of the investigation is Abidjan (Ivory Coast). 195 people were questioned among which 180 pupils-mothers on the basis of a not probability sample, exactly a sample of snowball. The observation and the semi-direct interview were used. The meditative data were handled (treated) statistically under the descriptive and inferential angle and qualitatively with an accent on the phenomenology. The results of the study show that pupils-mothers show difficulties of psychosocial adaptation: change of humor, depression, aggressiveness, anxiety, instability, led panics. These difficulties are strongly bound to the deficits of family and institutional supports (disappointment, rejection and powerlessness, low institutional coverage. These results validate the ecological theories and the social link. For a better personal and social adjustment, pupils-mothers, a strengthening of the supports within the framework of the solidarities turns out to be necessary.